2014
DOI: 10.31018/jans.v6i2.511
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant and antimicrobial activity of carotenoid pigment extracted from Sporobolomyces sp. isolated from natural source

Abstract: Abstract:The aim of the present study was to isolate and study about the antioxidant and antibacterial activity of carotenoid pigment. Sporobolomyces sp. isolated from the phyllosphere surface of rice plant has found to produce carotenoid pigment. The present investigation was carried out for antioxidant assays viz., DPPH, iron reducing and metal chelating activity. A steady increase in the antioxidant activities was observed in the carotenoid pigment with raising the pigment concentration. In the present stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 20 publications
2
33
0
Order By: Relevance
“…Among bacteria, Gram-negative bacteria had less sensitively compared to Gram-positive types, which represents higher resistance of Gram-negative bacteria to PER ( Table 1). The similar finding were observed by Umadevi and Krishnaveni [18]; and Manimala and Murugesan [19] for carotenoid pigment extracted from Micrococcus luteus KF532949 and Sporobolomyces sp. isolated from natural source, respectively, which reported that Gram-negative bacteria had higher resistance to the carotenoid pigments.…”
Section: Discussionsupporting
confidence: 74%
“…Among bacteria, Gram-negative bacteria had less sensitively compared to Gram-positive types, which represents higher resistance of Gram-negative bacteria to PER ( Table 1). The similar finding were observed by Umadevi and Krishnaveni [18]; and Manimala and Murugesan [19] for carotenoid pigment extracted from Micrococcus luteus KF532949 and Sporobolomyces sp. isolated from natural source, respectively, which reported that Gram-negative bacteria had higher resistance to the carotenoid pigments.…”
Section: Discussionsupporting
confidence: 74%
“…Microbial synthesis offers a promising method for production of carotenoids. This explains the increasing interest in production of microbial carotenoids as alternative for synthetic food colorants as well as for using it as antibacterial agent (Manimala et al, 2014).…”
Section: Issn: 2319-7706 Volume 6 Number 7 (2017) Pp 664-672mentioning
confidence: 99%
“…Phaffia, Rhodotorula, Cryptococcus and Sporobolomyces, fungi like Blakeslea trispora, and algae such as Dunaliella and Haematococcus and bacteria such as Flavobacterium and Micrococcus are reported to produce carotenoids (Manimala et al, 2014). Pigmented yeasts like Rhodotorula and Rhodosporidium produce the major carotenoid pigments viz.…”
Section: Issn: 2319-7706 Volume 6 Number 7 (2017) Pp 664-672mentioning
confidence: 99%
“…Pigments from other fungi such as Monodictys castaneae SVJM139 (Visalakchi and Muthumary, 2010); Sporobolomyces sp. (Manimala and Murugesan, 2014), Fusarium sp. (Geweely, 2011;Mani et al, 2015), Aspergillus sp.…”
Section: Antimicrobial Activities Of Fungal Pigmentsmentioning
confidence: 99%